Fate of airborne coagulase-negative staphylococci - Sudharsanam, Suchithra; Mathias, Shanthi; Barani, Ramya; Sugumar, Madhan; Janardhanan, Jeshina; Annamalai, Ravi; Swaminathan, Sandhya; Srikanth, Padma (International Journal of Infection Control, 2015)
Hospital indoor air can be a source for transmitting nosocomial infections in resource limited settings. This study was undertaken over two months period (February – March 2010) in Chennai, India, to 1) characterise bacteria isolated from indoor air of healthcare facility; and 2) establish whether environmental and clinical isolates are similar by molecular typing methods. Daily visits were made to microbiology laboratory to determine clustering of cases of nosocomial infections. Patients with illnesses related to respiratory tract and skin and soft tissues were included. Clinical strains (from laboratory) with similar antibiogram patterns were systematically stocked. Indoor air samples were collected from such locations by exposed plate method for 30 minutes. Growth was identified by standard microbiological procedures. Phenotypically similar strains were further subjected to genotyping by polymerase chain reaction and pulsed field gel electrophoresis (PFGE) to confirm similarity. Coagulase-negative Staphylococci (CNS) were only isolated from both environmental and clinical samples during the study period. Totally, 15 clinical and six environmental strains of CNS were isolated over two months. One airborne and one clinical strain, isolated subsequently from a patient in the same location, had similar phenotypic (biochemical and antibiogram) characteristics. Isolates were identified as Staphylococcus haemolyticus using API STAPH system (bioMe´rieux), and confirmed to be methicillin resistant CNS using appropriate primers. When subjected to typing by PFGE, they were found to be similar (F=0.51). This is the first study documenting the similarity of CNS of environmental and clinical origin, thus establishing the possibility of air as a source for transmitting nosocomial infections.